2013
DOI: 10.1186/1471-2431-13-23
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge translation of the HELPinKIDS clinical practice guideline for managing childhood vaccination pain: usability and knowledge uptake of educational materials directed to new parents

Abstract: BackgroundAlthough numerous evidence-based and feasible interventions are available to treat pain from childhood vaccine injections, evidence indicates that children are not benefitting from this knowledge. Unrelieved vaccination pain puts children at risk for significant long-term harms including the development of needle fears and subsequent health care avoidance behaviours. Parents report that while they want to mitigate vaccination pain in their children, they lack knowledge about how to do so. An evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
83
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(86 citation statements)
references
References 20 publications
2
83
0
1
Order By: Relevance
“…The search terms included immune pain, vaccine pain, pain relief, pain strategies, and pain techniques. Additionally, the references found in Taddio et al 6 were investigated for further research not found on the initial electronic search. Inclusion criteria consisted of studies investigating non-pharmacological pain-relieving strategies for vaccination-related pain in children aged 0-18 years.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The search terms included immune pain, vaccine pain, pain relief, pain strategies, and pain techniques. Additionally, the references found in Taddio et al 6 were investigated for further research not found on the initial electronic search. Inclusion criteria consisted of studies investigating non-pharmacological pain-relieving strategies for vaccination-related pain in children aged 0-18 years.…”
Section: Methodsmentioning
confidence: 99%
“…6 Further research is needed to identify specific barriers and HCP hesitancy to implement pain control with vaccinations in the outpatient setting. Discovering the gaps of implementing research into practice will assist with improved recommendations and provider education.…”
Section: Implications For Further Researchmentioning
confidence: 99%
See 3 more Smart Citations